The impact of audit committee and audit partner tenure on tax avoidance in banking - Dewi, Sari; Halim, Joice; Supriyanto, Supriyanto; Karjantoro, Handoko; Hendi, Hendi (Jurnal Akuntansi dan Auditing Indonesia, 2025)
The objective of our study is to examine the audit committees and audit partner tenure on tax avoidance. Additionally, our study investigates another variable that may influence subjective judgments of tax avoidance, such as return on assets, leverage, and firm size, on the relationship between audit committees and auditors as control variables. Using a quantitative approach, we focus on banking sector companies in Indonesia from 2018 to 2022. The results of this study show that audit partner tenure significantly affects tax avoidance, whereas audit quality does not have a notable influence. This study also shows that audit quality needs to be improved as a control mechanism to mitigate tax avoidance practices, particularly in the banking sector. Furthermore, audit partner tenure demonstrates a significant impact on tax avoidance. This study's theoretical and policy implications encourage company management to consider the potential long-term risks associated with extended audit partner tenure in the market.